Management of myofascial pain: a systematic review - Acing H. Mude; Imran Irsal (Journal of Dentomaxillofacial Science, 2020)
Objective: To investigate the current treatment on myofascial pain in the last 5 years.Methods: Electronic database were systematically searched in PubMed and Wiley to find articles related to treatment of myofascial pain that were published in last 5 years. ; Keyword or MESH that used in this study were management, treatment, myofascial pain, myofascial syndrome and temporomandibular disorder.  Results: There were 86 articles found in intial search, and only 17 were used as final articles after a selection using PICO questions. The number of female experiencing myofascial pain is 385 (94%) while men only 23 (6%) of the total sample of 408 people. The muscle involved n this study were masseter and temporal, with 3 (20 %) involved masseter and 12 (80 %) involved both muscle. The studies reported that the treatment use for this case were 7 (41%) with low-level laser therapy, 4 (23%) used treatment with drugs, 3 (17%) used occlusal device therapy and the other used dry needle, masseter nerve block and massage on temporal and mass muscle.Conclusion: This systematic review concluded that low level laser therapy was the most selected treatment in the last 5 years studies. Myofascial pain was predominantly found in female than male and muscle that involved in this treatment were masseter and temporalis muscle.